STUDENT CULTURE: APPROXIMATIONS BETWEEN SCHOOL PHYSICAL EDUCATION AND ETHNICAL DIVERSITY (Fiep Bulletin - online, 2015)
This work as a study focus on the student culture in the schools of the City of Porto Alegre Education Network (RME/Poa). The objective of this investigation is to understand the way that  ethnic diversity is manifested on school's physical education and the way this manifestation is articulated in the student culture. This research is characterized as a case study of qualitative approach, having as its main instruments of investigation observation, semi-structured interviews and  discussion groups with the students. Presently, observations of the physical education classes in a municipal school are being made, followed by notes in a field diary. Up to the moment it is possible to state that one of the factors that lead to a resistance by  some of the students in taking part of the activities that demand a higher body exposition originates from the mockery and nicknames given to  some physical characteristics that are considered depreciative in this group. On the other hand, we observe preliminarily that some African American students are protagonists in the groups where they act, exercising influence among the classmates, valuing their “blackness” and serving as examples of expression and body imposition.
Keywords: Student culture; Ethnic group; Physical Education